Kesejahteraan, pengeluaran pemerintah sektor kesehatan dan harapan hidup di Provinsi Aceh: Sebuah pendekatan data panel - Nanda Rahmi; Afdhal Putera (Jurnal Ekonomi Pembangunan, 2019)
This study to investigate the effect of health spending and Gross Regional Domestic Product (GRDP) on life expectancy in Aceh. The data are collected for 23 districts in Aceh over 4 years from 2012-2016. The analysis method uses a quantitative approach with applying a linear regression model with data panel. The findings of this study indicated that health spending and GRDP have a positive and significant effect on life expectancy. Furthermore, GRDP has a positive and significant relationship with life expectancy.